A expansão urbana da cidade do Salvador: transformações em uma metrópole da pobreza - SOARES, Priscila Oliveira (2016)
This paper explain which factors influenced the urban sprawl of the Salvador City throughout XX century, and check if is true the hypothesis that affirms the urbans transformations that have marked the city this long time and consequence of the loss of its national and regional role in economic terms especially in trade featuring a predominance of the scenario in the expansion of the occupation of the urban space by the low-income population. The theoretical tools used is based on geography, history, urban economics and theory of local development and through extensive research in primary and secondary sources the dissertation concludes if are maintained current conditions, at Salvador will increasingly lose its political and economic leading role in the country, in the role of poverty metropolis.